2021
DOI: 10.3390/cancers13174313
|View full text |Cite
|
Sign up to set email alerts
|

KCNJ5 Somatic Mutations in Aldosterone-Producing Adenoma Are Associated with a Greater Recovery of Arterial Stiffness

Abstract: Primary aldosteronism is the most common form of secondary hypertension and induces various cardiovascular injuries. In aldosterone-producing adenoma (APA), the impact of KCNJ5 somatic mutations on arterial stiffness excluding the influence of confounding factors is uncertain. We enrolled 213 APA patients who were scheduled to undergo adrenalectomy. KCNJ5 gene sequencing of APA was performed. After propensity score matching (PSM) for age, sex, body mass index, blood pressure, number of hypertensive medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…29 Genetically, the somatic mutation KCNJ5 has been shown to predict greater recovery of arterial stiffness after adrenalectomy. 30 Few studies have investigated the role of concomitant albuminuria on the progression of atherosclerosis. In this study, we investigated the role of albuminuria on arterial stiffness in PA patients at baseline and after PA-targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Genetically, the somatic mutation KCNJ5 has been shown to predict greater recovery of arterial stiffness after adrenalectomy. 30 Few studies have investigated the role of concomitant albuminuria on the progression of atherosclerosis. In this study, we investigated the role of albuminuria on arterial stiffness in PA patients at baseline and after PA-targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Genetically, the somatic mutation KCNJ5 has been shown to predict greater recovery of arterial stiffness after adrenalectomy. 30 …”
Section: Discussionmentioning
confidence: 99%
“…We previously found that KCNJ5 somatic mutations were predominant in patients with APA harboring somatic mutations [ KCNJ5 accounts for 90.6% of APA patients with somatic mutations ( 39 ) detected by traditional methods, 81.2% of APA patients with somatic mutations by sequencing combined with Sanger and IHC-guided biopsy and NGS ( 55 )]. Besides, the majority of studies investigating the clinical impacts of somatic mutations in APA patients are almost limited to comparing “ KCNJ5 mutations” with “non- KCNJ5 mutations” ( 40 , 41 , 46 , 48 , 57 60 ). The clinical data of other somatic mutations in APA patients is rare.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study ( 60 ) revealed lower brachial-ankle PWV (baPWV) in patients with KCNJ5 mutations compared to those without mutations before propensity score matching (PSM), but similar baPWV in both patients with and without mutations after matching for age, sex, BMI and hypertension status. After adrenalectomy, the decrease in baPWV in APA patients with KCNJ5 mutations was greater than that in those without mutations both before and after PSM.…”
Section: Kcnj5 Somatic Mutationsmentioning
confidence: 99%
“…Recent studies have shown that a significant proportion of aldosterone-producing adrenocortical adenomas harbor somatic mutations in a subset of genes mostly coding ion channels. The disease phenotype might be associated with some genetic variants, as the article by Chang et al shows greater recovery from arterial stiffness in adenomas harboring KCNJ5 somatic mutations [ 1 ]. The molecular features of a novel mutation in the ATP2B3 gene are presented in detail in the article by Liao et al [ 2 ].…”
mentioning
confidence: 99%